Quantitative and Qualitative Assessment of Pulmonary Emphysema with T2-Weighted PROPELLER MRI in a High-Risk Population Compared to Low-Dose CT - Meier-Schroers, Michael; Sprinkart, Alois Martin; Becker, Manuel; Homsi, Rami; Thomas, Daniel (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To determine the suitability of T2-weighted PROPELLER MRI for the assessment of pulmonary emphysema.Materials and Methods 60 participants in a lung cancer screening program (30 subjects with pulmonary emphysema, and 30 control subjects without emphysema) were included for this retrospective study. All subjects were examined with low-dose CT (LDCT) and MRI within the screening program. The use of a T2-weighted PROPELLER sequence for the assessment of emphysema was analyzed and correlated with the results of LDCT. The presence and the extent of pulmonary emphysema were first assessed qualitatively using a three-point score, and then quantitatively with a semi-automated software program to obtain emphysema indices.Results All 30 cases with pulmonary emphysema were accurately detected by MRI. There were 3 cases with emphysema according to MRI without emphysematous changes on LDCT (false-positive results). The qualitative scores as well as the emphysema indices were significantly higher in the emphysema group compared to the control group for MRI and LDCT (p < 0.001). Both the scores and the indices correlated significantly between MRI and LDCT (qualitative score of severity: r = 0.912/p < 0.001 in the emphysema group and r = 0.668/p < 0.001 in the control group; emphysema index: r = 0.960/p < 0.001 in the emphysema group and r = 0.746/p < 0.001 in the control group).Conclusion The presence and the extent of pulmonary emphysema may be assessed qualitatively and quantitatively by T2-weighted PROPELLER MRI with very good correlation to LDCT.Key Points: Citation Format
Keywords: CT; thorax; MR imaging